2018
DOI: 10.1111/cge.13449
|View full text |Cite
|
Sign up to set email alerts
|

Genomic duplication in the 19q13.42 imprinted region identified as a new genetic cause of intrauterine growth restriction

Abstract: We report findings from a male fetus of 26 weeks' gestational age with severe isolated intrauterine growth restriction (IUGR). Chromosomal microarray analysis (CMA) on amniotic fluid cells revealed a 1.06-Mb duplication in 19q13.42 inherited from the healthy father. This duplication contains 34 genes including ZNF331, a gene encoding a zinc-finger protein specifically imprinted (paternally expressed) in the placenta. Study of the ZNF331 promoter by methylation-specific-multiplex ligation-dependent probe amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Up to now, data on maternal or paternal ZNF331 expression are scarce and contradictory (Lambertini et al, 2012; Daelemans et al, 2010; Pollard et al, 2008; Pant et al, 2006), while the adjacent cluster of 46 miRNAs is paternally expressed in the placenta (Noguer-Dance et al, 2010). Recently, a paternally inherited duplication of 1.06 Mb, fully involving ZNF331 and C19MC , was stated to be pathogenic in a fetus with IUGR (Petre et al, 2018) that in our opinion might be ascribed to the duplication of the paternally expressed C19MC cluster. The fetus’s father, in turn, inherited the duplication from his mother mirroring, our patient 8 and her mother, but his phenotype is not described.…”
Section: Discussionmentioning
confidence: 69%
“…Up to now, data on maternal or paternal ZNF331 expression are scarce and contradictory (Lambertini et al, 2012; Daelemans et al, 2010; Pollard et al, 2008; Pant et al, 2006), while the adjacent cluster of 46 miRNAs is paternally expressed in the placenta (Noguer-Dance et al, 2010). Recently, a paternally inherited duplication of 1.06 Mb, fully involving ZNF331 and C19MC , was stated to be pathogenic in a fetus with IUGR (Petre et al, 2018) that in our opinion might be ascribed to the duplication of the paternally expressed C19MC cluster. The fetus’s father, in turn, inherited the duplication from his mother mirroring, our patient 8 and her mother, but his phenotype is not described.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, the two human-specific microRNA clusters (C19MC and C14MC), both appear to be imprinted (paternally and maternally expressed) for C19MC and C14MC, respectively, clusters that have been duly studied by the team of Yoel Sadovsky [45,89,152]. Recently, we identified duplication in the 19q13.42 imprinted region encompassing the C19MC cluster [153], from a male 26 weeks fetus with severe IUGR, suggesting that a double dose of the miRNA could contribute to the disease. This suggests links between miRNA regulation, imprinting status and the putative consequences for fetal health and growth.…”
Section: Epigenetics and Normal Placental Developmentmentioning
confidence: 99%
“…Generally speaking, postnatal cases usually presented a variety of clinical features with high speci city characterized by growth/psychomotor retardation and craniofacial dysmorphism. It was noteworthy that only ve cases were prenatally detected, presenting various degrees of fetal abnormalities [3,4,11,21,22]. However, our cases showed no fetal structural anomalies, which indicated that prenatal trisomy 19q cases might exhibit normal or abnormal ultrasound ndings.…”
Section: Discussionmentioning
confidence: 62%